A Note on Feedback Sequential Equilibria in a Lanchester Model with Empirical Application - Breton, Michèle; Jarrar, Ramla; Zaccour, Georges (Management Science, 2006)
We study in this paper dynamic equilibrium advertising strategies in a duopoly with asymmetric information structure and sequential play. The advertising model of Lanchester is used in a game where the relevant solution concept is feedback Stackelberg equilibrium, which is subgame perfect. An algorithm is devised for the computation of this equilibrium, and numerical results are reported and discussed. Using a data set from the cola market, we obtain the resulting advertising strategies and provide a comparison with closed-loop and open-loop Nash equilibria.